2023
DOI: 10.1044/2022_jslhr-22-00296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Capsaicin Atomization on Cough and Swallowing Function in Patients With Hemorrhagic Stroke: A Randomized Controlled Trial

Abstract: Background: Patients with hemorrhagic stroke have high mortality and disability rates. Nevertheless, early rehabilitation interventions can improve their outcomes. We aimed to apply capsaicin atomization as early intervention to patients with hemorrhagic stroke and explore improvements in cough and swallowing functions. Method: Patients with hemorrhagic stroke were randomly divided into the control group, which received routine care, and the interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…This is coherent with the current literature that described only a skin facial irritation self-limited without the use of drugs [12,[23][24]. Moreover, according to a previous study no alteration of the heart rate, respiratory rate, and oxygen saturation were observed during capsaicin administration [25].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is coherent with the current literature that described only a skin facial irritation self-limited without the use of drugs [12,[23][24]. Moreover, according to a previous study no alteration of the heart rate, respiratory rate, and oxygen saturation were observed during capsaicin administration [25].…”
Section: Discussionsupporting
confidence: 91%
“…The test can be used to evaluate the patient's ability to produce an effective cough and to detect any underlying problems with the cough reflex, with a documented excellent safety record in healthy volunteers as well as in patients with asthma, chronic obstructive pulmonary disease, pathologic cough, and other respiratory conditions [13][14]. This test has been applied either for diagnosis of cough reflex deficits or for therapeutic purposes in patients with neurogenic dysphagia [15], progressive supranuclear palsy [16], Parkinson's disease [17], and in patients with hemorrhagic stroke [18].…”
Section: Introductionmentioning
confidence: 99%
“…This is coherent with the current literature that has described only a skin facial irritation that is self-limited without the use of drugs [12,23,24]. Moreover, according to a previous study, no alteration of the heart rate, respiratory rate, or oxygen saturation was observed during capsaicin administration [18].…”
Section: Discussionsupporting
confidence: 91%
“…The test can be used to evaluate the patient's ability to produce an effective cough and to detect any underlying problems with the cough reflex, with a documented excellent safety record in healthy volunteers as well as in patients with asthma, chronic obstructive pulmonary disease, pathologic cough, and other respiratory conditions [13,14]. This test has been applied either for the diagnosis of cough reflex deficits or for therapeutic purposes in patients with neurogenic dysphagia [15], progressive supranuclear palsy [16], Parkinson's disease [17], and in patients with hemorrhagic stroke [18].…”
Section: Introductionmentioning
confidence: 99%